Betawi Ulama's Perception of The XXI Century Against Contraception Law Controversy in Population Control - Humaira, Aida; Rahman, Muh. Fudhail; Yaqub, Andi; Baharuddin, A. Zamakhsyari; Adhha, Nurul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
Legal issues regarding contraception and population control efforts to limit births and reduce overcrowding have not been without controversy. Differences in using naqli arguments and scientific, medical, and even political arguments make the discourse on family planning still hotly debated. This research will identify how Betawi Ulama's response in the XXI century to the law on the use of contraceptives and birth control through population control, along with the arguments and legal methods, they used to analyze the factors behind it and collect theoretical and empirical data related to social impacts/implications, from the Betawi Ulama's response to enacting the law on contraception and population control. The conclusion of this study will explain the positions, thoughts, and religious perspectives of Betawi Ulama in understanding various problems of Islamic law. Tend to think that is exclusive, inclusive, or moderate, especially in addressing the controversies of family planning law? This study took the capital city of DKI Jakarta as the sampling location, considering that the densest population in the country is in Jakarta, and it is very heterogeneous in terms of diversity and community characteristics. Population census data in 2010 shows that the capital city of DKI Jakarta is the largest city with the most populous population in Indonesia, around 9.6 million people. This research uses logical thinking, analysis with logic, induction, deduction, analogy, comparison and the like. The data in this study will be obtained through observation techniques, in-depth interviews with resource persons, and documentation.